Facilitated aortic valve replacement with complete sternotomy and minimal skin incision using endoscopy: a case of surgical report - Takahashi, Hiroaki; Gertner, Victor; Arif, Rawa; Kallenbach, Klaus; Karck, Matthias; Ruhparwar, Arjang (Annals of thoracic and cardiovascular surgery, 2014)
Although median sternotomy is the accepted approach to the heart for cardiac surgery, minimally invasive approaches including partial sternotomies have recently been developed. However, such strategies might lead to sternal overriding, instability, and fracture or division of the internal thoracic arteries. Furthermore, a full sternotomy would be required to address unpredictable intra- or postoperative complications. This article describes minimally invasive aortic valve replacement via full sternotomy and minimal skin incision using an endoscope.
Gesehen am 11.04.2016
Online March 26, 2013